Analysis of Supporting Factors to Prevent Stunting in Toddlers to Support Sustainable Development Goals - Nanik Yuliwati; Irma; Ranti Eka Putri; Ratna Ayu Untasih; Opik Yuliani (Postgraduate, University of Mataram, 2024)
Stunting is a target of the Sustainable Development Goals (SDGs), specifically within the second goal of eliminating hunger and all forms of malnutrition by 2030. This study aims to assess the influence of midwives, cadres, and family support on mothers' behavior in preventing stunting in toddlers in the UPT Puskesmas Jiput area. Using a quantitative analytical approach with a cross-sectional design, the study examines the relationships between these variables. The results show that the role of cadres significantly affects stunting prevention behavior in toddlers, with a p-value of 0.049. Family support also plays a crucial role, as indicated by a p-value of 0.021. Additionally, maternal motivation is significantly linked to stunting prevention behavior, with a p-value of 0.033. The study concludes that the roles of midwives, cadres, and family support significantly influence mothers' efforts to prevent stunting in toddlers. These findings highlight the importance of collaboration between healthcare workers, families, and the community in stunting prevention.